Analisis Pengukuran Waktu Kerja untuk Mengoptimalkan Jumlah Tenaga Kerja Pada Produksi Paper Bag di UD. LJS - Lutvi Oktavia; Handy Febri Satoto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD. LJS is a paper bag production company facing problems with the absence of standard time and workload imbalance, causing paper bag production targets to often not be achieved optimally. This study aims to establish standard working times, measure the real workload of operators, and formulate an efficient labor allocation through the Stopwatch Time Study approach and the Work Load Analysis (WLA) method. The evaluation results show a variation in standard time with the highest value in the Packing 2 process (16.72 seconds) and the lowest in the Cutting process (2.37 seconds). The WLA calculation results suggest increasing the number of workers from 20 to 31 people at work stations experiencing load accumulation. Based on cost comparison, the implementation of an overtime policy with a total expenditure of Rp. 107,640,000 is recommended as the best solution because it is more economical than adding new employees which requires a cost of Rp112,840,000.